Progress documentation of an exceptionally pronounced scalping injury Verlaufsdokumentation einer außergewöhnlich ausgeprägten „Scalping“-Verletzung - Isa, M.; Lenz, A. F.; Stenzel, M.; Pohle, R.; Banaschak, S.; Rothschild, M. A.; Boemers, T. M.; Kamphausen, T. (Rechtsmedizin, 2018)
An almost 3‑year-old girl was brought to the pediatric surgery department by her mother at night. The patient presented with the chief complaint of a massive, deformed helmet-shaped, fluctuating and pressure-sensitive swelling of the head. The history of the present injury allegedly began with nocturnal awakening to find the aforementioned physical findings and no visible scalp injury. The neurological examination was clinically uneventful. Anemia was present but did not require a blood transfusion. A coagulation disorder could be excluded by laboratory analysis. Other previous medical and surgical interventions were non-contributory. Cross-sectional magnetic resonance imaging (MRI) and ultrasound imaging of the skull revealed a marked subgaleal hematoma, without intracranial pathologies. Paravertebral hematomas and crescent-shaped superficial lesions were noted on the girl’s back, which could be explained by violently embracing the thorax. A non-accidental trauma as a result of a tangential, shearing force against the head was suspected. Subsequently, a broad subgaleal hematoma extending over the sutures was noted and was macromorphologically easily distinguishable from a locally limited cephalohematoma. Violent tearing of the scalp hair was suspected to be the most likely cause.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Child abuse; Eyelid diseases; Head injuries; closed; Magnetic resonance imaging; Subgaleal hematoma